Anmeldelser - Kjems, Thorkil (Danish Yearbook of Musicology, 1994)
Review of: Flute Concertos by Scheibe, Agrell & Hasse. Maria Bania (fløjte), Irene Spranger (fløjte) og Concerto Copenhagen under ledelse af Andrew Manze. CD Chandos CHAN 0535.